2015
DOI: 10.1007/s10787-015-0252-1
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin ameliorates experimental autoimmune encephalomyelitis by inhibiting Th1/Th17 response and cellular infiltration

Abstract: Simvastatin treatment promotes EAE clinical amelioration by inhibiting T cell proliferation and CNS infiltration by pathogenic Th1 and Th17 cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 61 publications
3
16
0
1
Order By: Relevance
“…37 In agreement with these findings the authors also reported lower central nervous system inflammatory mononuclear cell levels and less Th1 and Th17 cell infiltration in the central nervous system. 37 Furthermore, simvastatin diminished the proliferation of T cells co-cultured with primary microglial cells. Although the initial studies had suggested that statin treatment causes a Th2 induction, follow-up reports showed that atorvastatin treatment did not induce IL-4-producing Th2 cells in vivo.…”
Section: Statins In Mssupporting
confidence: 74%
See 2 more Smart Citations
“…37 In agreement with these findings the authors also reported lower central nervous system inflammatory mononuclear cell levels and less Th1 and Th17 cell infiltration in the central nervous system. 37 Furthermore, simvastatin diminished the proliferation of T cells co-cultured with primary microglial cells. Although the initial studies had suggested that statin treatment causes a Th2 induction, follow-up reports showed that atorvastatin treatment did not induce IL-4-producing Th2 cells in vivo.…”
Section: Statins In Mssupporting
confidence: 74%
“…36 A more recent study in which mice were immunized with myelin oligodendrocyte glycoprotein, showed that the treatment with simvastatin improved clinical disease scores. 37 Additionally, anti-inflammatory transforming growth factor-b mRNA expression was increased while IL-6, IL-12p40, IL-12p70, RANTES and macrophage inflammatory protein-1b were decreased. 37 In agreement with these findings the authors also reported lower central nervous system inflammatory mononuclear cell levels and less Th1 and Th17 cell infiltration in the central nervous system.…”
Section: Statins In Msmentioning
confidence: 98%
See 1 more Smart Citation
“…Simvastatin exhibits its immunomodulatory action by impacting the Th1 and Th17 as well as by modulation the dendritic cells (86, 87). …”
Section: Current and Possible Future Treatmentsmentioning
confidence: 99%
“…Some studies demonstrated that Treg cells can not properly infiltrate in CNS during the disease course (de Oliveira et al, 2015;Müller et al, 2007;Fritzsching et al, 2011). Inefficient migration of Treg cells to neuroinflammatory sites lead to profound implications (Keil et al, 2016;Buckner, 2010).…”
Section: Discussionmentioning
confidence: 99%